Houston Blue : The Story of the Houston Police Department - Roth, Mitchel P., 1953- (Book collections on Project MUSE., 2012)
Houston Blue offers the first comprehensive history of one of the nation's largest police forces, the Houston Police Department. Through extensive archival research and more than one hundred interviews with prominent Houston police figures, politicians, news reporters, attorneys, and others, authors Mitchel P. Roth and Tom Kennedy chronicle the development of policing in the Bayou City from its days as a grimy trading post in the 1830s to its current status as the nation's fourth largest city. Prominent historical figures who have brushed shoulders with Houston's Finest over the past 175 years.